Management of male erectile dysfunction: From the past to the future - Wang, Chang-Ming; Wu, Bao-Rui; Xiang, Ping; Xiao, Jun; Hu, Xue-Chun (Frontiers in Endocrinology, 2023)
Erectile dysfunction is a common disease of the male reproductive system, which seriously affects the life quality of patients and their partners. At present, erectile dysfunction is considered as a social-psychological-physiological disease with complex etiology and various treatment methods. Oral PDE5I is the first-line treatment for erectile dysfunction with the advantages of high safety, good effect and non-invasiveness. But intracavernosal injection, hormonal replacement therapy, vacuum erection device, penile prosthesis implantation can also be alternative treatments for patients have organic erectile dysfunction or tolerance to PDE5I. With the rapid development of technologies, some new methods, such as low-intensity extracorporeal shock wave and stem cell injection therapy can even repair the organic damage of the corpora cavernosa. These are important directions for the treatment of male erectile dysfunction in the future. In this mini-review, we will introduce these therapies in detail.